Fracture resistance of shell-steel reactor steel with mixed deformation modes for justification of extension of nuclear power plants lifetime - Pokrovsky Volodymyr V.; Sydiachenko Vyacheslav G.; Ezhov Vitaliy M. (Trudy Odesskogo Politehničeskogo Universiteta, 2017)
Preliminary thermomechanical loading promotes increase of resistance to brittle fracture of heat-resistant steels with fractures and is the fundamental basis of the perspective method of increasing the resource for ensuring safe operation of power reactor corps. In existing standards for calculating the strength of equipment of nuclear power plants, the calculation for fracture toughness is performed only for plane opening mode of fracture (mode I), but the plane of the fracture can have an arbitrary orientation with respect to external forces. Aim: The aim of the research is an experimental study of the effect of the preliminary thermomechanical load under modes I and II on the fracture toughness for modes II and I of reactor steels, respectively, as well as the preliminary thermomechanical load under the I + III mode for the fracture toughness under the I + III mode. Materials and Methods: Experimental studies of static fracture resistance were performed on samples on four-point bending (mode II), on cylindrical specimens torsion (mode III), and on a modified compact sample with an oblique fracture (mode I + III) for 15Ch2NMFA(II) and 15Ch2MFA(II) steels. Results: It is shown that the fracture toughness characteristics for transverse and longitudinal displacements (modes II, III) are smaller than for normal detachment (mode I) at a test temperature exceeding the brittle-viscous transition temperature, and vice versa, more when the test temperature is lower. It was found that the preliminary thermomechanical load under mode II causes an increase in the fracture toughness under mode II and a reduction in the fracture toughness under mode I for tempering embrittlement reactor steels. Under these conditions, this index practically does not change for plastic reactor steels. The established patterns show the need to modify regulatory documents to assess the ultimate bearing capacity of structural elements with fractures, in particular, the shells of nuclear power reactors, equipment of the 1st and 2nd circuits, pipelines.